2017
DOI: 10.1021/acssuschemeng.7b02110
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Ethylene from Carbon Dioxide and Water Using Intermittent Sunlight

Abstract: The large-scale deployment of efficient artificial photosynthesis systems to convert carbon dioxide (CO2) into carbon-based fuels and chemical feedstocks holds great promise as a way to ensure a carbon neutral cycle. While catalysts have been developed for the pertinent half-reaction of CO2 reduction to C2 molecules, an integrated system for this purpose has never been designed and built. In this work, we demonstrate an energetically efficient formation of ethylene directly from CO2 and water (H2O) using solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…This type of cathode contamination by metals from the counter electrode has been observed previously in CO2 electrolysis cells and appears to be only partially mitigated by the use of an anion conducting membrane. 24 Replacing the IrO2 counter electrode with Pt exacerbated the contamination effect with H2 production becoming dominant after only 2 days (Fig. S19c, ESI, shows XPS observation of Pt on the photocathode).…”
Section: Evaluation and Management Of Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This type of cathode contamination by metals from the counter electrode has been observed previously in CO2 electrolysis cells and appears to be only partially mitigated by the use of an anion conducting membrane. 24 Replacing the IrO2 counter electrode with Pt exacerbated the contamination effect with H2 production becoming dominant after only 2 days (Fig. S19c, ESI, shows XPS observation of Pt on the photocathode).…”
Section: Evaluation and Management Of Stabilitymentioning
confidence: 99%
“…Although far fewer in number compared to water splitting, there have been a number of recent demonstrations of solarpowered CO2R, some of which have reported overall energy conversion efficiencies above 1%. [18][19][20][21][22][23][24][25][26] Notably, most of these demonstrations employ photovoltaic elements which are isolated from the electrochemistry; exceptions are studies which use an illuminated photoanode to drive the water oxidation reaction (OER) with a dark cathode employed for CO2R. 20,21 Urbain et al reported a CO2 reduction prototype reactor containing a Si photoanode coupled to Ni foam as an OER catalyst and a Cu foam with Zn flakes as the cathode with a solar to syngas conversion efficiency of 4.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing CO 2 emission from the use of fossil fuels is urgently needed to prevent undesirable global warming . Using renewable electricity and catalysts for the electrochemical reduction of CO 2 to chemicals and fuels offers a promising approach to reduce our reliance on fossil fuels . Copper‐based catalysts are particularly attractive for such a purpose owing to their unique ability to reduce CO 2 to ethylene and ethanol .…”
Section: Introductionmentioning
confidence: 99%
“…Development of improved systems for CO 2 conversion has been an area of intense activity, with significant emphasis placed on EC design and on discovery of improved CO 2 reduction (4, 5) and H 2 O oxidation (6) catalysts based on nonprecious earthabundant elements. PV-EC systems for solar-driven CO 2 RRs have also been reported (7-9); however, only two such systems have provided appreciable selectivity for reduced carbon compounds containing C-C bonds (10,11). Among the PV-EC systems for CO 2 conversion, the most efficient one generates the C 1 feedstock CO (not hydrocarbons) using a GaInP/GaInAs/Ge PV cell (9).…”
Section: Co Co 2 Rr To C Rr To C 1 Products Products Co Co 2 Rr To C mentioning
confidence: 99%